Bequeathed? or Abandoned?! Analysis on the Maintenance of the Sportive Leisure's Equipments After the 59th Regional Games 2015 in São Jose do Rio Pardo-SP (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2018)
In 2015, São José do Rio Pardo City hosted the 59th Regional Games with a sports legacy address for citizenship. The present research sought to evaluate the legacy left from the maintenance of public sports leisure equipment six months after the event mentioned. This is a qualitative field study that crossed documentary analysis data with on-site visits to the equipment. The investments and improvements made could signal a sporting legacy and an incentive to leisure practices. However, when visiting the sites, it is noticed that the municipal public power did not perform basic maintenance activities. Some places are closer to “sportive abandonment" and deterioration due public neglect. Here we can mention the BMX racing track, for example. To host events of the Regional Games magnitude can contribute to the incentive to sports practice as long as the public power continues to develop policies and incentive rules aimed at the sector.